Species relationship in the genus Silene L. Section Auriculatae (Caryophyllaceae) based on morphology and RAPD analyses - Sheidai, Masoud; Gholipour, Abbas; Noormohammadi, Zahra (Acta Biologica Szegediensis, 2010)
Morphological and RAPD studies were performed on Silene species of the sect. Auriculatae growing in Iran for the first time using phenetic, parsimony and Bayesian analyses. Trees obtained differed in the species groupings although agreed in some parts. Parsimony and Bayesian analyses of morphological characters produced some clades which were not well supported by bootstrap and clade credibility values but UPGMA tree showed a high cophenetic correlation. Grouping based on morphological characters partly support the species affinity given in Flora Iranica. Out of 40 RAPD primers used 15 primer produced reproducible polymorphic bands. In total 347 bands were produced out of which 340 bands were polymorph and 7 bands were monomorph. Among the species studied S. goniocaula showed the highest number of RAPD bands (184), while S. commelinifolia var. isophylla showed the lowest number (123). Some of the species studied showed the presence of specific bands which may be use for species discrimination. NJ and Bayesian trees of RAPD data partly agree with morphological trees obtained.